2016
DOI: 10.1007/s11420-016-9508-6
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Open-Access Video-Based Orthopaedic Instructional Content for the Shoulder Physical Exam is Inconsistent

Abstract: Background: The internet has an increasing role in both patient and physician education. While several recent studies critically appraised the quality and accuracy of webbased written information available to patients, no studies have evaluated such parameters for open-access video content designed for provider use. Questions/Purposes: The primary goal of the study was to determine the accuracy of internet-based instructional videos featuring the shoulder physical examination. Methods: An assessment of quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Authors have found the posted videos to be reliable as a source of information despite the fact that some videos are inaccurate. 36 Of the studies, 13 focused on orthopedic conditions, assessing the reliability and educational value of videos on HV, 19 21 rotator cuff surgery, 14 anterior cruciate ligament reconstruction, 22 , 29 meniscus surgery, 28 knee arthroplasty, 30 lower-limb amputation, 31 physical shoulder examination, 37 femoroacetabular impingement, 38 and knee arthrocentesis. 39 All studies focused on orthopedic conditions were agreed that online videos provided poor information.…”
Section: Discussionmentioning
confidence: 99%
“…Authors have found the posted videos to be reliable as a source of information despite the fact that some videos are inaccurate. 36 Of the studies, 13 focused on orthopedic conditions, assessing the reliability and educational value of videos on HV, 19 21 rotator cuff surgery, 14 anterior cruciate ligament reconstruction, 22 , 29 meniscus surgery, 28 knee arthroplasty, 30 lower-limb amputation, 31 physical shoulder examination, 37 femoroacetabular impingement, 38 and knee arthrocentesis. 39 All studies focused on orthopedic conditions were agreed that online videos provided poor information.…”
Section: Discussionmentioning
confidence: 99%
“…Even though many high-quality videos are available, the quality of video clips is inconsistent and can be poor. 10,11 In a recent pilot study evaluating the impact of otology surgery videos on otolaryngology resident education, residents reported that they found that videos were highly useful and promoted self-efficacy and that they should be a high priority for a resident's surgical preparation. 3 In light of the increased use of videos in medical and surgical teaching, more high-quality medical learning videos must be made available.…”
Section: Discussionmentioning
confidence: 99%
“…As these types of platforms are openly accessible to both content creators and consumers, the quality of the materials can sometimes be questionable. 3,25 Students in this study were provided with resources that had been developed with, and reviewed by, the lecturer associated with the unit. This provided some assurance as to the quality of the content and regulation over version control, attributes that may not be present in open-access forums.…”
Section: Discussionmentioning
confidence: 99%